1960
DOI: 10.1071/bi9600541
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies on Pole Cells and Midgut Differentiation in Diptera

Abstract: Highly localized irradiation with ultraviolet of the posterior polar region of eggs of Drosophila melanogaster and Lucilia cuprina in pre.pole cell and pole cell stages results in reduction in numbers of the cuprophilic cells of the middle midgut as well as in reduction of gonad size and number. Carefully timed eggs were exposed to dosages of ultraviolet (from a source giving about 90 per cent. at wavelength 2536 A) ranging from 1200 to 2400 I-' W sec/cm2 over periods of 2-4 min. Treatments at the time of acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

1962
1962
1985
1985

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…In 1964, Jura considered the origin, fate and effects of treatment of pole cells in D. virilis. Finally, Poulson and Waterhouse (1960) established the essential role of the pole cells in Diptera with respect to the development of a fertile imago in these holometabolous insects. They also implicated pole cells in the differentiation of specialized portions of the midgut, a site of pole cell migration.…”
Section: Introductionmentioning
confidence: 99%
“…In 1964, Jura considered the origin, fate and effects of treatment of pole cells in D. virilis. Finally, Poulson and Waterhouse (1960) established the essential role of the pole cells in Diptera with respect to the development of a fertile imago in these holometabolous insects. They also implicated pole cells in the differentiation of specialized portions of the midgut, a site of pole cell migration.…”
Section: Introductionmentioning
confidence: 99%
“…In these instances RNA-containing cytoplasmic granules are segregated into a small number of cells that have been shown to become the primordial germ cells. By utilizing procedures that remove this specific region of the egg (6, 7), destroy it with ultraviolet light (8)(9)(10)(11)(12), or displace it by centrifugation (13-15), many workers have been able to verify the determinative role of a specific region of the egg for forming germ cells. Furthermore, Smith (16) has been able to restore the capacity of vegetal cytoplasm of frog eggs to produce germ cells by injecting "germinal plasm" into eggs that had been sterilized by UV-irradiation.…”
mentioning
confidence: 99%
“…Subsequently, some of these cells differentiate into primordial germ cells within the embryonic gonad, while others probably participate in forming the midgut (10). Many workers (e.g., 8,[10][11][12] have shown that UV-irradiation or removal of the posterior polar plasm of eggs before the presence of nuclei in this region results in embryos devoid of primordial germ cells and, consequently, in flies that are sterile. Direct confirmation of the embryological evidence that pole cells become germ cells has been achieved by transplanting genetically marked pole cells to a differently marked host embryo and obtaining offspring from the transplanted cells (17).…”
mentioning
confidence: 99%
“…The cellular pellet is carefully removed with a hook of fine tungsten wire and cut into 10-30 pieces (depending on the size of the pellet) with a tungsten needle. The pieces are implanted into the body cavity of adult Oregon-R females (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) (27) and labial (28) discs respectively, as a result of transdetermination.…”
Section: Culture Methodsmentioning
confidence: 99%
“…The first few cells arise at the posterior pole after about 2.5 hr of development at 250C. These cells are designated as pole cells and give rise to the primordial germ cells (15) and the cuprophilic cells of the gut (16). At about 3 hr of development, the majority of the nuclei migrate to the periphery of the egg into the cortical cytoplasm, where they line up in a single layer.…”
mentioning
confidence: 99%